FORMATION OF STUDENTS' VALUE ATTITUDE TO NATURE AS A COMPONENT OF ECOLOGICAL CULTURE - Галина Жирська (Ternopil Volodymyr Hnatiuk National Pedagogical University, 2014)
The article presents a substantiation of the connection of value attitude to nature with ecological culture of an individual and the need to apply new approaches to its formation in the conditions of environmental crisis. The content, structure and peculiarities of student's evaluation activity on the formation of their value attitude to nature were analyzed. The power of modern methods and means of natural and scientific education for the organization of emotional and evaluative ecology oriented activity in educational process at secondary schools has been revealed.